2011
DOI: 10.1539/joh.l10125
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Chronic Noise Exposure Induced Spatial Learning and Memory Deficits in Young Male Sprague‐Dawley Rats

Abstract: Objective: Noise has always been an important environmental public health issue for mankind. Although reports exist on hippocampaldependent spatial learning and memory (LM) impairment due to noise, there are only a few studies that have examined the effects of recovery from noise stress on LM impairments. Therefore, the present study investigated the effects of recovery from chronic noise exposure on LM deficits. Materials and Methods: In this study, the detrimental effects of noise stress on young male rats i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 23 publications
6
22
1
3
Order By: Relevance
“…As Mc2r is the sole receptor for ACTH, this observation may provide insight into how environmental noise exposure may modulate the stress response of the hippocampus. Studies elsewhere have reported that chronic environmental noise exposure is associated with disrupted function of the hippocampus, an extra-auditory structure of the central nervous system, thereby inducing memory deficit and cognition impairment (Cheng et al, 2011;Chengzhi et al, 2011;Manikandan et al, 2006;Uran et al, 2012Uran et al, , 2010Cui et al, 2012Cui et al, , 2013. Indeed, Jáuregui-Huerta et al showed that chronic exposure to environmental noise in the early stages of life produces a long-lasting reduction in cell proliferation in the hippocampus in the neurogenic and non-neurogenic hippocampal regions (Kraus and Canlon, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As Mc2r is the sole receptor for ACTH, this observation may provide insight into how environmental noise exposure may modulate the stress response of the hippocampus. Studies elsewhere have reported that chronic environmental noise exposure is associated with disrupted function of the hippocampus, an extra-auditory structure of the central nervous system, thereby inducing memory deficit and cognition impairment (Cheng et al, 2011;Chengzhi et al, 2011;Manikandan et al, 2006;Uran et al, 2012Uran et al, , 2010Cui et al, 2012Cui et al, , 2013. Indeed, Jáuregui-Huerta et al showed that chronic exposure to environmental noise in the early stages of life produces a long-lasting reduction in cell proliferation in the hippocampus in the neurogenic and non-neurogenic hippocampal regions (Kraus and Canlon, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, orientin treatment markedly reversed the reductions of NE and DA induced by chronic noise exposure. The NE and DA neurotransmitter systems are involved in learning and memory processes, and a substantial part of learning and memory impairment is due to changes in neurotransmission [41]. Therefore, the reversal of the noise-induced alteration of the levels of NE and DA may contribute to orientin's effect in improving the cognitive impairments induced by chronic noise exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Noise exposure exceeds 90 dB has been reported to be a source of stressor [4]. The adverse impact of noise on learning, memory and hippocampal neurogenesis has been reported by previous studies [5][6][7][8][9]. The mechanisms underlying the decline of memory after noise exposure are not entirely clear.…”
Section: Introductionmentioning
confidence: 96%
“…Noise exposure may induce the generation of free radicals and deplete the activities of antioxidant enzymes in plasma and tissues [10,11]. Previous studies have shown that increased oxidative stress is the cause of neuronal degeneration in auditory nuclei as well as the brain regions critical for cognitive functions [6,12,13].…”
Section: Introductionmentioning
confidence: 99%